Optical glass, glass prefabricated part, optical element and optical instrument

The optical glass composition with controlled components and ratios enhances hardness and light transmittance, addressing the durability and imaging quality issues of existing glasses for vehicle-mounted imaging and security applications.

CN119241062APending Publication Date: 2025-01-03CDGM OPTICAL GLASS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411350471.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing optical glasses used in vehicle-mounted imaging and security applications lack sufficient hardness and light transmittance, which affects their durability and imaging quality.

Method used

An optical glass composition comprising specific weight percentages of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5, Gd2O3, TiO2, RO, Rn2O, WO3, ZnO, Al2O3, Yb2O3, and GeO2, with controlled ratios and ranges to enhance hardness and light transmittance, along with the use of clarifiers like Sb2O3, SnO, SnO2, and CeO2 to improve clarity.

Benefits of technology

The glass exhibits a refractive index of 1.87 to 1.94, Abbe number of 33 to 41, Knoop hardness above 670×10^7 Pa, and high light transmittance with λ70 and λ5 values below 410nm and 370nm respectively, offering improved durability and imaging quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062213690000121
    Figure BDA0005062213690000121
  • Figure BDA0005062213690000122
    Figure BDA0005062213690000122
  • Figure BDA0005062213690000141
    Figure BDA0005062213690000141
Patent Text Reader

Abstract

The invention discloses optical glass, a glass prefabricated part, an optical element and an optical instrument, and relates to the technical field of optical glass. The optical glass comprises the following components in percentage by weight: 1-15% of SiO2; 5 to 25 percent of B2O3; the content of La2O3 is 35%-60%; 4 to 25 percent of Y2O3; zrO2: 2%-15%; 3 to 20 percent of Nb2O5; 0 to 10 percent of Gd2O3; 0 to 10 percent of TiO2; 0 to 5 percent of Ta2O5; 0-8% of RO; 0 to 8% of Rn2O; 0 to 5 percent of WO3; znO: 0 to 10%; 0 to 8 percent of Al2O3; 0 to 10 percent of Yb2O3; 0 to 5 percent of GeO2; 0-2% of a clarifying agent; the ratio of (Y2O3 + Nb2O5) / La2O3 is 0.2 to 1.0; rO is one or more of MgO, CaO, SrO and BaO; the Rn2O is one or more of Li2O, Na2O and K2O; and the clarifying agent is one or more of Sb2O3, SnO, SnO2 and CeO2. The optical glass provided by the invention has relatively high hardness and light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optical glass, and in particular to an optical glass, a glass preform, an optical element and an optical instrument. Background Art

[0002] Lenses made of high-refractive-index low-dispersion optical glass can be combined with lenses made of ultra-low-dispersion optical glass to correct aberrations and make the optical system compact, so they occupy a very important position in the design of optical systems. In recent years, with the rapid development of vehicle-mounted imaging, monitoring and security, etc., the demand for high-refractive-index low-dispersion optical glass continues to increase. At the same time, optical glass used in the fields of vehicle-mounted imaging, monitoring and security is expected to have a higher hardness to resist the wear or impact of sand and stones during vehicle driving and extend the service life of the optical glass; on the other hand, the optical glass is also required to have a higher light transmittance to improve the imaging quality. Therefore, it is urgent to develop a high-refractive-index low-dispersion optical glass with higher hardness and light transmittance.

[0003] This application is a divisional application for the invention patent application with application number 202211030902.0, application date August 26, 2022, and name “Optical Glass and Optical Elements”. Summary of the invention

[0004] The main purpose of the present application is to provide an optical glass, a glass preform, an optical element and an optical instrument, aiming to solve the technical problem that the hardness and light transmittance of the existing optical glass need to be improved.

[0005] To achieve the above-mentioned purpose, the present application proposes an optical glass, which comprises the following components by weight percentage: SiO2: 1-15%; B2O3: 5-25%; La2O3: 35-60%; Y2O3: 4-25%; ZrO2: 2-15%; Nb2O5: 3-20%; Gd2O3: 0-10%; TiO2: 0-10%; Ta2O5: 0-5%; RO: 0-8%; Rn2O: 0-8%; WO3: 0-5%; ZnO: 0-10%; Al2O3: 0-8%; Yb2O3: 0-10%; GeO2: 0-5%; clarifier: 0-2%;

[0006] Among them, (Y2O3+Nb2O5) / La2O3 is 0.2~1.0;

[0007] The RO is one or more of MgO, CaO, SrO and BaO;

[0008] The Rn2O is one or more of Li2O, Na2O, and K2O;

[0009] The clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2;

[0010] The refractive index nd of the optical glass is 1.87 to 1.94, the Abbe number vd is 33 to 41, and λ 70 410nm or less, λ5 is 370nm or less, Knoop hardness H K 670×10 7 Pa or above.

[0011] Optionally, the contents of the components are, by weight percentage: SiO2: 2-12%; B2O3: 7-20%; La2O3: 40-60%; Y2O3: 6-22%; ZrO2: 3-12%; Nb2O5: 5-15%; Gd2O3: 0-7%; TiO2: 0-8%; Ta2O5: 0-3%; RO: 0-3%; Rn2O: 0-3%; WO3: 0-3%; ZnO: 0-5%; Al2O3: 0-4%; Yb2O3: 0-5%; GeO2: 0-3%; clarifier: 0-1%.

[0012] Optionally, the contents of the components are, by weight percentage: SiO2: 4-10%; B2O3: 9-16%; La2O3: 42-55%; Y2O3: 8-20%; ZrO2: 4-10%; Nb2O5: 7-11%; Gd2O3: 0-5%; TiO2: 0-5%; Ta2O5: 0-1%; RO: 0-2%; Rn2O: 0-2%; WO3: 0-2%; ZnO: 0-2%; Al2O3: 0-2%; Yb2O3: 0-3%; GeO2: 0-1%; clarifier: 0-0.5%.

[0013] Optionally, the content of each component satisfies at least one of the following conditions:

[0014] La2O3+Y2O3+Gd2O3 is 60-70%;

[0015] (SiO2+Y2O3) / B2O3 is 1.0 to 2.0;

[0016] Y2O3 / (SiO2+ZrO2) is 0.5 to 2.0;

[0017] (Y2O3+Nb2O5) / La2O3 is 0.35-0.65;

[0018] Nb2O5 / B2O3 is 0.6~1.5.

[0019] Optionally, the content of each component satisfies at least one of the following conditions:

[0020] TiO2 / (Y2O3+Nb2O5) is less than 0.3;

[0021] (RO+Rn2O) / SiO2 is less than 0.5;

[0022] ZnO / Y2O3 is less than 0.2;

[0023] (Ta2O5+Gd2O3) / Nb2O5 is less than 0.8.

[0024] Optionally, the components of the optical glass do not contain one or a combination of two or more of RO, Rn2O, WO3, ZnO, Al2O3 and GeO2.

[0025] Optionally, the refractive index nd of the optical glass is 1.89 to 1.91, the Abbe number vd is 36 to 39, and λ 70 is less than 395nm, λ5 is less than 355nm, Knoop hardness H K 690×10 7 Pa or more; the thermal expansion coefficient of the optical glass α 20 / 120℃ 80×10 -7 / K or less, Young's modulus E is 11500×10 7 Pa~13000×10 7 Pa; water resistance stability of the optical glass D W The weather resistance is CR class 2 or above, and the bubble degree is A or above.

[0026] The present application also proposes a glass preform, which is made of the above optical glass.

[0027] The present application also proposes an optical element, which is made of the above optical glass, or made of the above glass preform.

[0028] The present application also proposes an optical instrument, which contains the above optical glass and / or the above optical element.

[0029] The optical glass of the present application uses SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5, Gd2O3, TiO2, Ta2O5, RO, Rn2O, WO3, ZnO, Al2O3, Yb2O3, GeO2 and clarifier as raw materials. SiO2 has the functions of adjusting optical constants, improving chemical stability of glass, maintaining viscosity suitable for molten glass, reducing abrasion and corrosion to refractory materials. B2O3 can improve the fusibility and devitrification resistance of glass, which is beneficial to lowering the transition temperature of glass. La2O3 is an effective component for improving the refractive index of glass, and has a significant effect on improving the chemical stability and devitrification resistance of glass. Y2O3 can improve the refractive index and devitrification resistance of glass and adjust the Young's modulus of glass. ZrO2 can improve the viscosity, hardness, refractive index and chemical stability of optical glass, and can also reduce the thermal expansion coefficient of glass. Nb2O5 is a high refractive and high dispersion Components can increase the refractive index and resistance to devitrification of glass, and reduce the thermal expansion coefficient of glass. Gd2O3 can increase the refractive index and chemical stability of glass. TiO2 can increase the refractive index of glass. Ta2O5 has the effect of increasing the refractive index and enhancing the resistance to devitrification of glass. Alkaline earth metal oxide RO can adjust the optical constants of glass and optimize the chemical stability of glass. Alkali metal oxide Rn2O can reduce the transition temperature of glass, adjust the optical constants and high-temperature viscosity of glass, and improve the meltability of glass. WO3 can increase the refractive index and mechanical strength of glass. ZnO can adjust the refractive index and dispersion of glass, and reduce the high-temperature viscosity and transition temperature of glass. Al2O3 can improve the chemical stability of glass. Yb2O3 is also a component that gives glass high refractive index and low dispersion properties. GeO2 has the effect of increasing the refractive index and resistance to devitrification. Clarifiers can improve the clarification effect of glass and increase the bubble degree of glass. The present application further improves the hardness and light transmittance of the glass by selecting the above components and rationally designing their contents, and controlling the ratio of the total content of Y2O3 and Nb2O5 to the content of La2O3 (Y2O3+Nb2O5) / La2O3 within the range of 0.2 to 1.0. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0031] In view of the technical problems existing in the above-mentioned prior art, the embodiment of the present application provides an optical glass, which comprises the following components by weight percentage: SiO2: 1-15%; B2O3: 5-25%; La2O3: 35-60%; Y2O3: 4-25%; ZrO2: 2-15%; Nb2O5: 3-20%; Gd2O3: 0-10%; TiO2: 0-10%; Ta2O5: 0-5%; RO: 0-8%; Rn2O: 0-8%; WO3: 0-5%; ZnO: 0-10%; Al2O3: 0-8%; Yb2O3: 0-10%; GeO2: 0-5%; clarifier: 0-2%;

[0032] Among them, (Y2O3+Nb2O5) / La2O3 is 0.2~1.0;

[0033] The RO is one or more of MgO, CaO, SrO and BaO;

[0034] The Rn2O is one or more of Li2O, Na2O, and K2O;

[0035] The clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2;

[0036] The refractive index nd of the optical glass is 1.87 to 1.94, the Abbe number vd is 33 to 41, and λ 70 410nm or less, λ5 is 370nm or less, Knoop hardness H K 670×10 7 Pa or above.

[0037] As an implementation method of the present application, the contents of the components are, by weight percentage: SiO2: 2-12%; B2O3: 7-20%; La2O3: 40-60%; Y2O3: 6-22%; ZrO2: 3-12%; Nb2O5: 5-15%; Gd2O3: 0-7%; TiO2: 0-8%; Ta2O5: 0-3%; RO: 0-3%; Rn2O: 0-3%; WO3: 0-3%; ZnO: 0-5%; Al2O3: 0-4%; Yb2O3: 0-5%; GeO2: 0-3%; clarifier: 0-1%.

[0038] As an implementation method of the present application, the contents of the components are, by weight percentage: SiO2: 4-10%; B2O3: 9-16%; La2O3: 42-55%; Y2O3: 8-20%; ZrO2: 4-10%; Nb2O5: 7-11%; Gd2O3: 0-5%; TiO2: 0-5%; Ta2O5: 0-1%; RO: 0-2%; Rn2O: 0-2%; WO3: 0-2%; ZnO: 0-2%; Al2O3: 0-2%; Yb2O3: 0-3%; GeO2: 0-1%; clarifier: 0-0.5%.

[0039] As an implementation method of the present application, the content of each component satisfies at least one of the following conditions:

[0040] La2O3+Y2O3+Gd2O3 is 60-70%;

[0041] (SiO2+Y2O3) / B2O3 is 1.0 to 2.0;

[0042] Y2O3 / (SiO2+ZrO2) is 0.5 to 2.0;

[0043] (Y2O3+Nb2O5) / La2O3 is 0.35-0.65;

[0044] Nb2O5 / B2O3 is 0.6~1.5.

[0045] As an implementation method of the present application, the content of each component satisfies at least one of the following conditions:

[0046] TiO2 / (Y2O3+Nb2O5) is less than 0.3;

[0047] (RO+Rn2O) / SiO2 is less than 0.5;

[0048] ZnO / Y2O3 is less than 0.2;

[0049] (Ta2O5+Gd2O3) / Nb2O5 is less than 0.8.

[0050] As an implementation method of the present application, the components of the optical glass do not contain one or a combination of two or more of RO, Rn2O, WO3, ZnO, Al2O3 and GeO2.

[0051] Specifically, SiO2 has the functions of adjusting optical constants, improving chemical stability of glass, maintaining viscosity suitable for molten glass, reducing abrasiveness and erosion of refractory materials. In the present application, the above effects can be obtained by containing 1-15% SiO2. Preferably, the content of SiO2 is 2% or more, and more preferably, the content of SiO2 is 4% or more. If the content of SiO2 is too high, the melting difficulty of glass increases and the transition temperature rises. Therefore, in the present application, the upper limit of the content of SiO2 is 15%, preferably 12%, and more preferably 10%.

[0052] B2O3 can improve the melting property and resistance to devitrification of glass, which is beneficial to lowering the transition temperature of glass. The present application can obtain the above-mentioned effect by containing 5-25% B2O3, preferably containing more than 7% B2O3, and more preferably containing more than 9% B2O3. If the content of B2O3 is too high, the chemical stability of the glass will deteriorate, especially the water resistance will deteriorate, and the refractive index and light transmittance of the glass will decrease. Therefore, the content of B2O3 is less than 25%, preferably less than 20%, and more preferably less than 16%;

[0053] La2O3 is an effective component for improving the refractive index of glass, and has a significant effect on improving the chemical stability and devitrification resistance of glass. If its content is less than 35%, it is difficult to achieve the required optical constants. If the content is higher than 65%, the devitrification tendency of the glass increases and the thermal stability deteriorates. Therefore, the content of La2O3 is 35-60%. Therefore, the content of La2O3 is limited to 35-65%, preferably 40-60%, and more preferably 42-55%.

[0054] Y2O3 can improve the refractive index and devitrification resistance of glass and adjust the Young's modulus of glass. The present application obtains the above effects by containing 4% or more of Y2O3. If the content exceeds 25%, the chemical stability and weather resistance of glass deteriorate. Therefore, the content of Y2O3 is 4-25%, preferably 6-22%, more preferably 8-20%, and further preferably 11-20%.

[0055] ZrO2 can improve the viscosity, hardness, refractive index and chemical stability of optical glass, and can also reduce the thermal expansion coefficient of glass. When the content of ZrO2 is too high, the devitrification resistance of glass is reduced, the melting difficulty is increased, the melting temperature is increased, and inclusions appear inside the glass and the light transmittance is reduced. Therefore, the content of ZrO2 in this application is 2-15%, preferably 3-12%, and more preferably 4-10%;

[0056] Nb2O5 is a high-refractive and high-dispersion component, which can improve the refractive index and devitrification resistance of glass and reduce the thermal expansion coefficient of glass. In the present application, the above effect is obtained by containing more than 3% of Nb2O5. The lower limit of the content of Nb2O5 is preferably 5%, and the lower limit is more preferably 7%. However, when the content of Nb2O5 exceeds 20%, the thermal stability and weather resistance of the glass are reduced, and the light transmittance is reduced. Therefore, the upper limit of the content of Nb2O5 is 20%, preferably 15%, and more preferably 11%.

[0057] Gd2O3 can improve the refractive index and chemical stability of glass, but if its content is higher than 10%, the devitrification resistance and abrasion resistance of glass will deteriorate, so the content of Gd2O3 is 0-10%, preferably 0-7%, and more preferably 0-5%;

[0058] TiO2 can increase the refractive index of glass, but too high a content will greatly reduce the dispersion coefficient and increase the tendency of crystallization, and even cause the glass to be obviously colored. Therefore, the TiO2 content is limited to 0-10%, preferably 0-8%, and more preferably 0-5%;

[0059] Yb2O3 is also a component that gives the glass high refractive and low dispersion properties. If its content exceeds 10%, the anti-crystallization performance of the glass decreases. Therefore, the content of Yb2O3 is 0-10%, preferably 0-5%, and more preferably 0-3%. In some embodiments, it is further preferred that Yb2O3 is not contained.

[0060] Alkaline earth metal oxide RO can adjust the optical constants of glass and optimize the chemical stability of glass, but when its content is high, the devitrification resistance of glass decreases, so the RO content is limited to 0-8%, preferably 0-3%, and more preferably 0-2%;

[0061] The alkali metal oxide Rn2O can lower the transition temperature of the glass, adjust the optical constants and high temperature viscosity of the glass, and improve the melting property of the glass. However, when the content of Rn2O is high, the devitrification resistance and chemical stability of the glass are reduced. Therefore, the content of Rn2O is 0 to 8%, preferably 0 to 3%, and more preferably 0 to 2%. In some embodiments, it is further preferred that Rn2O is not contained.

[0062] WO3 can improve the refractive index and mechanical strength of glass. If the content of WO3 exceeds 5%, the thermal stability of the glass decreases and the resistance to devitrification decreases. Therefore, the upper limit of the content of WO3 is 5%, preferably 3%, and more preferably 2%. In some embodiments, it is further preferred that WO3 is not contained.

[0063] ZnO can adjust the refractive index and dispersion of the glass, reduce the high temperature viscosity and transition temperature of the glass. If the content of ZnO is too high, the difficulty of glass molding increases and the anti-crystallization performance deteriorates. Therefore, the content of ZnO is 0-10%, preferably 0-5%, and more preferably 0-2%. In some embodiments, it is further preferred that ZnO is not contained.

[0064] Ta2O5 has the function of increasing the refractive index and improving the devitrification resistance of glass, but if its content is too high, the thermal stability of the glass will decrease, the density will increase, and the optical constants will be difficult to control within the desired range; on the other hand, compared with other components, the price of Ta2O5 is very expensive. From the perspective of practicality and cost, its usage should be minimized. Therefore, the content of Ta2O5 in this application is limited to 0-5%, preferably 0-3%, and more preferably 0-1%; in some embodiments, it is further preferred that Ta2O5 is not contained;

[0065] Al2O3 can improve the chemical stability of glass, but when its content exceeds 8%, the meltability and light transmittance of glass deteriorate. Therefore, the content of Al2O3 in the present application is 0-8%, preferably 0-4%, and more preferably 0-2%. In some embodiments, it is further preferred that Al2O3 is not contained.

[0066] GeO2 has the function of improving the refractive index and resistance to devitrification, but if its content is too high, the chemical stability of the glass will decrease; on the other hand, compared with other components, GeO2 is very expensive. From the perspective of practicality and cost, its usage should be minimized. Therefore, the content of GeO2 in this application is limited to 0-5%, preferably 0-3%, and more preferably 0-1%; in some embodiments, it is further preferred that GeO2 is not contained.

[0067] In some embodiments, the ratio of the total content of SiO2 and Y2O3 SiO2+Y2O3 to the content of B2O3 (SiO2+Y2O3) / B2O3 is controlled within the range of 1.0 to 2.0, which can increase the bubble degree and light transmittance of the glass and further optimize the hardness of the glass.

[0068] In some embodiments, by controlling the total content of La2O3, Y2O3 and Gd2O3 La2O3+Y2O3+Gd2O3 within the range of 60 to 70%, the glass can more easily obtain a desired refractive index and Abbe number, and optimize the devitrification resistance and weather resistance of the glass.

[0069] In some embodiments, the ratio of the Y2O3 content to the total content of SiO2 and ZrO2 SiO2+ZrO2, Y2O3 / (SiO2+ZrO2), is controlled within the range of 0.5 to 2.0, which can further optimize the abrasiveness of the glass, prevent the hardness of the glass from decreasing, and further optimize the weather resistance and Young's modulus of the glass.

[0070] In some embodiments, the ratio of the total content of Y2O3 and Nb2O5 to the content of La2O3 (Y2O3+Nb2O5) / La2O3 is controlled within the range of 0.35 to 0.65, which is beneficial to improving the hardness and light transmittance of the glass and further optimizing the Young's modulus and bubble degree of the glass.

[0071] In some embodiments, the ratio of Nb2O5 to B2O3, Nb2O5 / B2O3, is controlled between 0.6 and 1.5, which can optimize the chemical stability and light transmittance of the glass, and further optimize the bubble degree and thermal expansion coefficient of the glass.

[0072] In some embodiments, the ratio of TiO2 content to the total content of Y2O3 and Nb2O5, TiO2 / (Y2O3+Nb2O5), is controlled to be below 0.3, which can improve the anti-crystallization and weather resistance of the glass and further optimize the thermal expansion coefficient and hardness of the glass.

[0073] In some embodiments, the ratio of the total content of RO and Rn2O RO+Rn2O to the content of SiO2 (RO+Rn2O) / SiO2 is controlled below 0.5, which can optimize the weather resistance and striae of the glass and make it easier for the glass to obtain a suitable Young's modulus.

[0074] In some embodiments, the ratio of ZnO content to Y2O3 content, ZnO / Y2O3, is controlled to be below 0.2, which can improve the bubble degree and chemical stability of the glass, reduce the thermal expansion coefficient of the glass, and optimize the abrasiveness of the glass.

[0075] In some embodiments, by controlling the ratio of the total content of Ta2O5 and Gd2O3 Ta2O5+Gd2O3 to the content of Nb2O5 (Ta2O5+Gd2O3) / Nb2O5 to below 0.8, the chemical stability of the glass can be improved while reducing the thermal expansion coefficient of the glass, and further optimizing the density and Young's modulus of the glass.

[0076] In some embodiments, the present application can improve the clarification effect of the glass and the bubble degree of the glass by containing 0-2% of one or more components of Sb2O3, SnO, SnO2, and CeO2 as a clarifier. The content of the clarifier is preferably 0-1%, and the content of the clarifier is more preferably 0-0.5%. Since the component types and contents of the optical glass of the present application are reasonably designed and its bubble degree is excellent, it is further preferred that no clarifier is contained in some embodiments. In addition, when the Sb2O3 content exceeds 2%, the glass tends to have reduced clarification performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the molding mold. Therefore, the present application preferably has a Sb2O3 content of 0-2%, more preferably 0-1%, further preferably 0-0.5%, and further preferably no Sb2O3; SnO and SnO2 can also be used as clarifiers, but when their content exceeds 2%, the glass tends to increase in coloring, or when the glass is heated, softened, and molded again, Sn It will become the starting point of crystal nucleation and produce a tendency of devitrification. Therefore, the SnO2 content of the present application is preferably 0-2%, more preferably 0-1%, further preferably 0-0.5%, and further preferably does not contain SnO2; the SnO content is preferably 0-2%, more preferably 0-1%, further preferably 0-0.5%, and further preferably does not contain SnO; the effect and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-2%, more preferably 0-1%, further preferably 0-0.5%, and further preferably does not contain CeO2.

[0077] In the specific implementation process, in the optical glass of the present application, the oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, even if they exist alone or are contained in a small amount after compounding, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of the present application to improve the visible light transmittance effect. Therefore, in particular, optical glass with requirements for transmittance at wavelengths in the visible light region does not contain oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo.

[0078] In the specific implementation process, the oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, except for the inevitable mixing, it is preferred that they are actually not contained. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present application can be manufactured, processed and discarded.

[0079] In the specific implementation process, in order to achieve environmental friendliness, the optical glass of the present application preferably does not contain As2O3 and PbO.

[0080] As an implementation method of the present application, the refractive index nd of the optical glass is 1.89 to 1.91, the Abbe number vd is 36 to 39, and λ 70 is less than 395nm, λ5 is less than 355nm, Knoop hardness H K 690×10 7 Pa or more; the thermal expansion coefficient of the optical glass α 20 / 120℃ 80×10 -7 / K or less, Young's modulus E is 11500×10 7 Pa~13000×10 7 Pa; water resistance stability of the optical glass D W The weather resistance is CR class 2 or above, and the bubble degree is A or above.

[0081] Specifically, the refractive index (nd) and Abbe number (vd) of the optical glass are tested according to the method specified in GB / T 7962.1-2010. The refractive index nd of the optical glass of the present application is preferably 1.90, and the Abbe number vd is preferably 37-38.

[0082] The short-wave transmission spectrum characteristics of optical glass are expressed by the color degree (λ 70 and λ5) indicates that λ 70 It refers to the wavelength when the glass transmittance reaches 70%, λ 70 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 70%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I in The amount expressed by λ also includes the transmittance of the surface reflection loss on the above surface of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 70 A small value of means that the glass itself is less colored and has a high light transmittance. 70 It is below 395nm and λ5 is below 355nm.

[0083] Knoop hardness of optical glass (H K) Tested according to the test method specified in GB / T7962.18-2010. The Knoop hardness of the optical glass in this application is H K 690×10 7 Pa or above.

[0084] Thermal expansion coefficient of optical glass (α 20 / 120℃ ) The data at 20-120°C is tested according to the method specified in GB / T7962.16-2010. The thermal expansion coefficient α of the optical glass of the present application 20 / 120℃ 80×10 -7 / K or less.

[0085] Young's modulus (E) is calculated by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity according to the following formula:

[0086]

[0087] G=Vsp

[0088] Where: E is Young's modulus, Pa;

[0089] G is the shear modulus, Pa;

[0090] V T is the shear wave velocity, m / s;

[0091] V S is the longitudinal wave velocity, m / s;

[0092] ρ is the glass density, g / cm 3 .

[0093] The Young's modulus E of the optical glass of the present application is preferably 12000×10 7 Pa~12500×10 7 Pa.

[0094] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0095] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.

[0096] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, and alternately cycle every 1 hour at 40-50°C. After 15 cycles, the weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1 below:

[0097] Table 1

[0098]

[0099] In some embodiments, the weather resistance (CR) of the optical glass of the present application is Class 2 or above, preferably Class 1.

[0100] The bubble degree of the optical glass is tested according to the method specified in GB / T7962.8-2010. The bubble degree of the optical glass of the present application is above grade A, preferably above grade A0, and more preferably above grade A. 00 class.

[0101] In the specific implementation process, the method for preparing the optical glass of the present application comprises the following steps:

[0102] After the above raw materials are prepared according to conventional methods, the prepared materials are put into a melting furnace (such as a platinum or platinum alloy crucible) at 1200-1450° C. for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0103] The embodiment of the present application further provides a glass preform, which is made of the above-mentioned optical glass.

[0104] Specifically, the optical glass can be used to make a glass preform by means of direct drop molding, grinding, or hot press molding. That is, the molten optical glass can be directly drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the glass preform can be made by making a preform for molding from the optical glass, hot press molding the preform, and then grinding the preform to make a glass preform.

[0105] It should be noted that the means for preparing the glass preform are not limited to the above-mentioned means.

[0106] The embodiments of the present application further provide an optical element, which is made of the above optical glass, or made of the above glass preform.

[0107] Specifically, the optical glass or glass preform of the present application can be formed into a preform, and the preform can be used to perform re-hot pressing, precision stamping, etc. to make various optical elements. The optical element has the excellent properties of optical glass and can be used as various lenses, prisms and other optical elements with high optical value. For example, it can be used as various lenses such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses with spherical or aspherical lens surfaces.

[0108] The embodiments of the present application also provide an optical instrument, which contains the above-mentioned optical glass and / or contains the above-mentioned optical element.

[0109] Specifically, the optical elements formed by the optical glass of the present application can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment, and monitoring equipment.

[0110] It should be noted that, in the present application, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present application are decomposed and converted into oxides during melting, the total amount of the oxide material is taken as 100%.

[0111] Unless otherwise indicated in specific circumstances, the numerical ranges listed in this application include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0112] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0113] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0114] Example Optical Glass

[0115] According to the contents of each component shown in Table 2-Table 4, 24 types of optical glasses were prepared using the above-mentioned optical glass preparation method, and the characteristics of each optical glass were measured according to the test method described in this application, and the measurement results are shown in Table 2-Table 4.

[0116] Table 2

[0117]

[0118]

[0119]

[0120] Table 3

[0121]

[0122]

[0123] Table 4

[0124]

[0125]

[0126] It can be seen from Tables 2 to 4 that the optical glass prepared in this application has high hardness and light transmittance, and the highest Knoop hardness can reach 715×10 7 Pa or above, λ 70 The lowest is 386nm, and the lowest λ5 is 345nm, indicating that the optical glass has a high refractive index and excellent light transmittance.

[0127] Example Glass Preform

[0128] The optical glass obtained in Examples 1-24 is used to make glass preforms of various lenses, prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, by means of processing such as grinding, or molding such as re-hot pressing, precision stamping, etc.

[0129] Example Optical Components

[0130] The preforms obtained in the above embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.

[0131] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0132] Embodiment Optical Instrument

[0133] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.

[0134] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.

Claims

1. An optical glass, characterized in that: The invention comprises the following components by weight percentage: SiO2: 1-15%; B2O3: 5-25%; La2O3: 35-60%; Y2O3: 4-25%; ZrO2: 2-15%; Nb2O5: 3-20%; Gd2O3: 0-10%; TiO2: 0-10%; Ta2O5: 0-5%; RO: 0~8%; Rn2O: 0~8%; WO3: 0~5%; ZnO: 0-10%; Al2O3: 0-8%; Yb2O3: 0-10%; GeO2: 0-5%; Clarifier: 0-2%; Among them, (Y2O3+Nb2O5) / La2O3 is 0.2~1.0; The RO is one or more of MgO, CaO, SrO and BaO; The Rn2O is one or more of Li2O, Na2O, and K2O; The clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2; The refractive index nd of the optical glass is 1.87 to 1.94, the Abbe number vd is 33 to 41, and λ 70 410nm or less, λ5 is 370nm or less, Knoop hardness H K 670×10 7 Pa or above.

2. The optical glass according to claim 1, characterized in that: The contents of the components are as follows by weight: SiO2: 2-12%; B2O3: 7-20%; La2O3: 40-60%; Y2O3: 6-22%; ZrO2: 3-12%; Nb2O5: 5-15%; Gd2O3: 0-7%; TiO2: 0-8%; Ta2O5: 0-3%; RO: 0-3%; Rn2O: 0-3%; WO3: 0-3%; ZnO: 0-5%; Al2O3: 0-4%; Yb2O3: 0-5%; GeO2: 0-3%; clarifier: 0-1%.

3. The optical glass according to claim 1, characterized in that: Calculated by weight percentage, the contents of the components are: SiO2: 4-10%; B2O3: 9-16%; La2O3: 42-55%; Y2O3: 8-20%; ZrO2: 4-10%; Nb2O5: 7-11%; Gd2O3: 0-5%; TiO2: 0-5%; Ta2O5: 0-1%; RO: 0-2%; Rn2O: 0-2%; WO3: 0-2%; ZnO: 0-2%; Al2O3: 0-2%; Yb2O3: 0-3%; GeO2: 0-1%; clarifier: 0-0.5%.

4. The optical glass according to any one of claims 1 to 3, characterized in that: The content of each component satisfies at least one of the following conditions: La2O3+Y2O3+Gd2O3 is 60-70%; (SiO2+Y2O3) / B2O3 is 1.0 to 2.0; Y2O3 / (SiO2+ZrO2) is 0.5 to 2.0; (Y2O3+Nb2O5) / La2O3 is 0.35-0.65; Nb2O5 / B2O3 is 0.6~1.

5.

5. The optical glass according to any one of claims 1 to 3, characterized in that: The content of each component satisfies at least one of the following conditions: TiO2 / (Y2O3+Nb2O5) is less than 0.3; (RO+Rn2O) / SiO2 is less than 0.5; ZnO / Y2O3 is less than 0.2; (Ta2O5+Gd2O3) / Nb2O5 is less than 0.

8.

6. The optical glass according to any one of claims 1 to 3, characterized in that: The components of the optical glass do not contain one or a combination of two or more of RO, Rn2O, WO3, ZnO, Al2O3 and GeO2.

7. The optical glass according to any one of claims 1 to 6, characterized in that: The refractive index nd of the optical glass is 1.89 to 1.91, the Abbe number vd is 36 to 39, and λ 70 is less than 395nm, λ5 is less than 355nm, Knoop hardness H K 690×10 7 Pa or more; the thermal expansion coefficient of the optical glass α 20 / 120℃ 80×10 -7 / K or less, Young's modulus E is 11500×10 7 Pa~13000×10 7 Pa; water resistance stability of the optical glass D W The weather resistance is CR class 2 or above, and the bubble degree is A or above.

8. A glass preform, characterized in that: Made of the optical glass according to any one of claims 1 to 7.

9. An optical element, characterized in that: The optical glass is made of the optical glass described in any one of claims 1 to 7, or the glass preform described in claim 8.

10. An optical instrument, characterized in that: The optical glass according to any one of claims 1 to 7 and / or the optical element according to claim 9.

Citation Information

Cited By

  • Oxide optical glass and preparation method thereof

    CN120681956A